If $\sin A + {\left( {\sin A} \right)^2} = 1$, then the value of the expression \[\left[ {{{\left( {\cos A} \right)}^2} + {{\left( {\cos A} \right)}^4}} \right]\] is
$
{\text{A}}{\text{. 1}} \\
{\text{B}}{\text{. }}\dfrac{1}{2} \\
{\text{C}}{\text{. 2}} \\
{\text{D}}{\text{. 3}} \\
$
Answer
Verified
504.3k+ views
Hint: Here, we will be using the formula ${\left( {\sin \theta } \right)^2} + {\left( {\cos \theta } \right)^2} = 1$ in order to determine the values of \[{\left( {\cos A} \right)^2}\] and \[{\left( {\cos A} \right)^4}\] from the given equation which is $\sin A + {\left( {\sin A} \right)^2} = 1$ and then ultimately the expression whose value is required will appear as the LHS of the given equation.
Complete step-by-step answer:
Given, $
\sin A + {\left( {\sin A} \right)^2} = 1{\text{ }} \to {\text{(1)}} \\
\Rightarrow \sin A = 1 - {\left( {\sin A} \right)^2}{\text{ }} \to {\text{(2)}} \\
$
As we know that
$
{\left( {\sin \theta } \right)^2} + {\left( {\cos \theta } \right)^2} = 1 \\
\Rightarrow {\left( {\cos \theta } \right)^2} = 1 - {\left( {\sin \theta } \right)^2}{\text{ }} \to {\text{(3)}} \\
$
Replacing the angle $\theta $ with angle $A$ in equation (3), we get
$ \Rightarrow {\left( {\cos A} \right)^2} = 1 - {\left( {\sin A} \right)^2}{\text{ }} \to {\text{(4)}}$
Clearly, the RHS of both the equations (2) and (4) are the same so the LHS of both the equations will also be equal.
\[ \Rightarrow \sin A = {\left( {\cos A} \right)^2}{\text{ }} \to {\text{(5)}}\]
So, the value of the expression \[\left[ {{{\left( {\cos A} \right)}^2} + {{\left( {\cos A} \right)}^4}} \right]\] can be determined by little modification as under.
\[\left[ {{{\left( {\cos A} \right)}^2} + {{\left( {\cos A} \right)}^4}} \right] = \left[ {{{\left( {\cos A} \right)}^2} + {{\left( {\cos A} \right)}^2} \times {{\left( {\cos A} \right)}^2}} \right]\]
Using equation (5), we get
\[
\Rightarrow \left[ {{{\left( {\cos A} \right)}^2} + {{\left( {\cos A} \right)}^4}} \right] = \left[ {\sin A + \left( {\sin A} \right) \times \left( {\sin A} \right)} \right] \\
\Rightarrow \left[ {{{\left( {\cos A} \right)}^2} + {{\left( {\cos A} \right)}^4}} \right] = \left[ {\sin A + {{\left( {\sin A} \right)}^2}} \right] \\
\]
Finally using the given equation (1), we get
\[ \Rightarrow \left[ {{{\left( {\cos A} \right)}^2} + {{\left( {\cos A} \right)}^4}} \right] = 1\]
Therefore, the value of the expression \[\left[ {{{\left( {\cos A} \right)}^2} + {{\left( {\cos A} \right)}^4}} \right]\] is 1.
Hence, option A is correct.
Note: In this particular problem, we obtained the value of \[{\left( {\cos A} \right)^2}\] in terms of \[\sin A\]using the given equation and some trigonometric formula. From there we represented the expression whose value is required in terms of \[{\left( {\cos A} \right)^2}\] which is ultimately converted in terms of \[\sin A\].
Complete step-by-step answer:
Given, $
\sin A + {\left( {\sin A} \right)^2} = 1{\text{ }} \to {\text{(1)}} \\
\Rightarrow \sin A = 1 - {\left( {\sin A} \right)^2}{\text{ }} \to {\text{(2)}} \\
$
As we know that
$
{\left( {\sin \theta } \right)^2} + {\left( {\cos \theta } \right)^2} = 1 \\
\Rightarrow {\left( {\cos \theta } \right)^2} = 1 - {\left( {\sin \theta } \right)^2}{\text{ }} \to {\text{(3)}} \\
$
Replacing the angle $\theta $ with angle $A$ in equation (3), we get
$ \Rightarrow {\left( {\cos A} \right)^2} = 1 - {\left( {\sin A} \right)^2}{\text{ }} \to {\text{(4)}}$
Clearly, the RHS of both the equations (2) and (4) are the same so the LHS of both the equations will also be equal.
\[ \Rightarrow \sin A = {\left( {\cos A} \right)^2}{\text{ }} \to {\text{(5)}}\]
So, the value of the expression \[\left[ {{{\left( {\cos A} \right)}^2} + {{\left( {\cos A} \right)}^4}} \right]\] can be determined by little modification as under.
\[\left[ {{{\left( {\cos A} \right)}^2} + {{\left( {\cos A} \right)}^4}} \right] = \left[ {{{\left( {\cos A} \right)}^2} + {{\left( {\cos A} \right)}^2} \times {{\left( {\cos A} \right)}^2}} \right]\]
Using equation (5), we get
\[
\Rightarrow \left[ {{{\left( {\cos A} \right)}^2} + {{\left( {\cos A} \right)}^4}} \right] = \left[ {\sin A + \left( {\sin A} \right) \times \left( {\sin A} \right)} \right] \\
\Rightarrow \left[ {{{\left( {\cos A} \right)}^2} + {{\left( {\cos A} \right)}^4}} \right] = \left[ {\sin A + {{\left( {\sin A} \right)}^2}} \right] \\
\]
Finally using the given equation (1), we get
\[ \Rightarrow \left[ {{{\left( {\cos A} \right)}^2} + {{\left( {\cos A} \right)}^4}} \right] = 1\]
Therefore, the value of the expression \[\left[ {{{\left( {\cos A} \right)}^2} + {{\left( {\cos A} \right)}^4}} \right]\] is 1.
Hence, option A is correct.
Note: In this particular problem, we obtained the value of \[{\left( {\cos A} \right)^2}\] in terms of \[\sin A\]using the given equation and some trigonometric formula. From there we represented the expression whose value is required in terms of \[{\left( {\cos A} \right)^2}\] which is ultimately converted in terms of \[\sin A\].
Recently Updated Pages
Master Class 12 Business Studies: Engaging Questions & Answers for Success
Master Class 12 English: Engaging Questions & Answers for Success
Master Class 12 Economics: Engaging Questions & Answers for Success
Master Class 12 Chemistry: Engaging Questions & Answers for Success
Master Class 12 Social Science: Engaging Questions & Answers for Success
Class 12 Question and Answer - Your Ultimate Solutions Guide
Trending doubts
10 examples of friction in our daily life
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE
State and prove Bernoullis theorem class 11 physics CBSE
Pigmented layer in the eye is called as a Cornea b class 11 biology CBSE
State the laws of reflection of light